Loss of ATP-dependent lysine uptake in the vacuolar membrane vesicles of Saccharomyces cerevisiae ypq1∆ mutant. Issue 7 (3rd July 2014) - Sekito, Takayuki; Nakamura, Kyosuke; Manabe, Kunio; Tone, Junichi; Sato, Yumika; Murao, Nami; Kawano-Kawada, Miyuki; Kakinuma, Yoshimi
Abstract: Saccharomyces cerevisiae Ypq1p is a vacuolar membrane protein of the PQ-loop protein family . We found that ATP-dependent uptake activities of amino acids by vacuolar membrane vesicles were impaired by ypq1 ∆ mutation. Loss of lysine uptake was most remarkable, and the uptake was recovered by overproduction of Ypq1p. Ypq1p is thus involved in transport of amino acids into vacuoles.